Alteridade e morte em "Páramo", de Guimarães Rosa - PEREIRA JÚNIOR, José Antônio Braga (Universidade Federal do Pará, 2017)
This dissertation aims to investigate the relation between the themes of otherness and death in “Páramo”, by João Guimarães Rosa, based on Hall (2006), Bhabha (1998), both about the concept of otherness, and Ariès (2012) and Levinas (2000), both about the concept of death. Published in Estas Estórias (1969), “Páramo” is a singular writing among the works of Guimarães Rosa, because it is the most autobiographic text of the author and is set on a urban space of a foreing city. In this tale, a brazilian ambassador is sent to an andean city where he has to execute a diplomatic service, but after to be shoked by extreme otherness of that place he begins feeling a process of decentering of his identity, that culminates with premonition of his death and a need of renovation of Being. The relevance of this research is that it brings new discussions about the inevitable relation between Me, Other and death in the text of “Páramo”, so that we can reflete about the philosofical and cultural outspread of this relation. This research is divide into three parts: the first part of this study will deal with the concepts of otherness and death acordding the authors related above. In the second part of this study we will launch a reflection about the philosofical and cultural problems based on the intertwined relation between otherness and death on the text of “Páramo”, accomplishing a dialogue with the concepts and categories of Being, Other and the Stranger. In the third and last part of this research, we will realize a dialogue between the conceptions presented in this research and the perspectives presented in most relevant works published about “Páramo”, as studies from Hector Olea Galaviz (1987), Maria Thereza Scher Pereira (2007 e 2009), Bairón Escallón (2011, 2012 e 2013), Luciano Antônio (2013), Gisálio Cerqueira Filho (2013), Betina Cunha (2014), Maria Magnabosco (2003), Edson Oliveira (2010) e Paulo Moreira (2013), aiming to contribute to studies dedicated to this narrative of João Guimarães Rosa.